Governance and coordination of business cartels - Carlos Mario Muñoz Maya; Rafael Pérez-Uribe; María Teresa Ramírez Garzón; Olga Lucia Diaz Villamizar (Revista Venezolana de Gerencia)
This research proposes an exploratory analysis of the dynamics of governance and coordination within business cartels, which enable the stability of these organizations outside the realm of formal legal control and despite the threat of cheating and detection. To this end, a case study was conducted to examine how informal mechanisms contribute to stability in 13 Colombian business cartels. The results underscore that explaining cartel stability requires considering social and economic mechanisms that induce trust, ranging from negotiation to coercion. These combined mechanisms contribute to maintaining cohesion and compliance with agreements within the cartel. The management of business cartels presents two main approaches: an economic approach and a social approach. The economic approach is based on distrust among parties and the need to implement monitoring and retaliatory mechanisms. The social approach highlights mutual trust, negotiation, and mediation for conflict resolution, thereby fostering cooperation.